CONSEQUENCES OF THE CROWN CRISIS’ INFLUENCE ON ENTREPRENEURSHIP IN UKRAINE - SAVCHENKO, OLENA; NETREBA, ANGELINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Entrepreneurship development is considered one of the most important tasks for economy of every country. Challenges of the external environment create additional obstacles. We can say that makes impossible the development of entrepreneurship of Ukraine. Ukraine’s economy, inherited from the USSR, still remains monopolized. Entrepreneurship occupies an insignificant place in its structure. While in Europe small and medium-sized businesses play an important role in socio-economic development, the number of people employed in small businesses in Europe is about 90%. Small and medium-sized enterprises usually generate at least 50-70% of GDP. The Ukrainian economy is far from this indicator, as we have determined. The complexity of the situation is exacerbated by the fact that today businesses is faced with many additional problems and difficulties. The number of business entities in 2018-2020 significantly decreased as a result of the lockdowns, reduction of effective demand, etc. Which areas of entrepreneurship suffered the most - was described in the article. The study of small business activities in the context of the COVID-19 pandemic identified the following risks: closure; liquidity deficit; large-scale reduction and narrowing of the structure of consumer demand; breaking the chains of value added and supply; loss of the domestic market; Uncertainty in foreign markets, especially regarding post-quarantine volumes, terms and opportunities for export recovery As we believe, all the possible potential for business development in Ukraine is far from exhausted. The main stimulus for the development of entrepreneurship in Ukraine is state support. And only when the state pays attention to the problems of domestic entrepreneurship and provides its support, we can say that entrepreneurship in Ukraine is developing and bearing profits.